2017
DOI: 10.1139/tcsme-2017-1045
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATION OF CO2 ABSORPTION PERFORMANCE IN A GAS-LIQUID TWO-PHASE FLOW ATOMIZER ON THE BASIS OF A GAS DIFFUSION MODEL

Abstract: Experimental and analytical studies of CO2 absorption performance are carried out in a gas-liquid two-phase flow atomizer on the basis of a gas diffusion model. The gas-liquid two-phase flow atomizer with high spray efficiency and low power consumption has been applied to CO2 absorption. Experiments for the CO2 absorption were conducted in an isolated room and the results showed that, the mist sprayed by the improved atomizer can effectively reduce the CO2 concentration. Furthermore, a CO2 diffusion model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Six simulations were carried out with six turbulence models: the standard k-, realized k-, RNG k-, standard k-ω, BSL k-ω and SST k-ω models. The simulation conditions are as follows: l in = 20.5 mm, l out = 20.5 mm, d 1 = 21 mm, d 2 = 5 mm, D = 13.8 mm and φ = 0.1 (Yao et al, 2017). Finally, the simulated results of these six cases were compared with the measured experimental data (Yao et al, 2017) in Figure 3 to check the evaluation accuracy of the different turbulence models.…”
Section: Influence Of Air Flow Velocity On the Absorbed Watermentioning
confidence: 99%
See 4 more Smart Citations
“…Six simulations were carried out with six turbulence models: the standard k-, realized k-, RNG k-, standard k-ω, BSL k-ω and SST k-ω models. The simulation conditions are as follows: l in = 20.5 mm, l out = 20.5 mm, d 1 = 21 mm, d 2 = 5 mm, D = 13.8 mm and φ = 0.1 (Yao et al, 2017). Finally, the simulated results of these six cases were compared with the measured experimental data (Yao et al, 2017) in Figure 3 to check the evaluation accuracy of the different turbulence models.…”
Section: Influence Of Air Flow Velocity On the Absorbed Watermentioning
confidence: 99%
“…This is because the high-speed air flow will generate a negative pressure at the orifice when the air flows through the orifice, and then the increased negative pressure will result in an increase in the water velocity of the inlet. The simulated values of the six turbulence models are compared with the experimental values (Yao et al, 2017) in this paper, as shown in Figure 3. It is found that the simulated values of the SST k-ω model are consistent with the experimental values, and the relative error is 6.7%.…”
Section: Influence Of Air Flow Velocity On the Absorbed Watermentioning
confidence: 99%
See 3 more Smart Citations